Numerical research on hydrodynamic characteristics of end cover of pressure exchanger. Issue 1 (May 2016) - Jiao, L; Lin, H T; Shi, Y; Liu, Z C; Feng, Z M; Li, G S
Abstract: To investigate hydrodynamic performance of the end cover under different inclined angles, a series of 3-Dimensional geometric models of the end cover with different inclined angles were built by Creo. The maximum inclined angle is 32 degrees and the minimum is 6 degrees. Numerical simulations by solving the Navier-Stokes equation, coupled with the "k-ɛ" turbulence model, were carried out. At last, regressive analysis method is used to deal with the result data. The data obtained by simulation were mainly analysed from three aspects. They are cause of the driving torque, drive efficiency and inclined angle of flow channel. The results show that the driving torque is formed mainly by the positive pressure of the water, and the influence of the viscous force on the driving torque of the rotor is negligible. What's more, both driving torque and pressure difference decrease with the increase of inclined angle in the form of power function. The driving efficiency increases in form of logarithmic function with the increase of inclined angle. This research has a great significance in the control of rotational speed of rotor and revealed the relationship between the driving torque of the rotor and the flow channel of the end cover.